Comparative histochemical evaluation of mucins expression in fetal esophagus and adenocarcinomas of the gastroesophageal junction - Vernygorodskyi, S.; Rekun, T.; Zhuchenko, P. (Experimental Oncology, 2018)
Aim: To study and compare the expression patterns of mucins in the fetal gastroesophageal junction (GEJ) region and adenocarcinomas of the GEJ in adults using histochemical method. Material and Methods: To reveal the expression of different mucins, tissue sections from formalin-fixed paraffin-embedded tissue blocks of fetal GEJ and carcinomas of GEJ were stained by the following histological stains: hematoxylin and eosin, periodic acid-Schiff (PAS), alcian blue (AB), pH 2.5, combined AB-PAS, and combined AB-Aldehyde Fuchsin (AB/AF). Results: Expression of mucins within the developing fetal GEJ has been demonstrated (gestational age 5–38 weeks). We studied histochemical features of neoplastic cells in carcinomas of GEJ from 90 adult patients. The results showed that in gastric type expression of neutral mucins dominated especially in well differentiated (G1) adenocarcinomas and corresponded to the last three months of GEJ development, while in the intestinal and mixed type significant acid mucins expression was detected in moderate (G2) and poorly (G3) differentiated adenocarcinomas and corresponded to 17–25 weeks of GA. No significant coincidence in mucins expression was observed in signet ring cell carcinomas in relation to GA. Conclusion: Our data suggest that decrease of neutral mucins level can be considered reliable phenotypic marker of poor prognosis of GEJ adenocarcinomas. Study of the developmental expression of mucin genes may improve understanding of the malignant transformation of esophageal tissue. Key Words: mucin expression, gastroesophageal junction, adenocarcinoma.